The times are changing: temporal shifts in patterns of fish invasions in central European fresh waters. Issue 1 (26th October 2012) - Rabitsch, W.; Milasowszky, N.; Nehring, S.; Wiesner, C.; Wolter, C.; Essl, F.
<x xml:space="preserve">Abstract</x> This study examines the invasion history of alien fish species based on exhaustive national data sets on fish invasions of two contiguous central European countries (Germany and Austria). Fifteen alien fish species are currently established in both countries, constituting 14 and 17% of the total freshwater fish fauna of Germany and Austria, respectively. In both countries, six alien species are present, but not established. The status of five alien species in Germany and three species in Austria remains unknown. Accumulation rates of alien fish species have increased in recent decades with >50% of them reported after 1971. North America and Asia were the primary sources of alien fish species in Germany and Austria up to the 1980s, whereas European species of Ponto‐Caspian origin dominate now. Fisheries (including aquaculture) and the animal trade were responsible for most earlier introductions, whereas waterways were the main pathway for recent invaders. The extent of the spatial distribution of alien species was positively correlated with residence time, i.e. the time elapsed since the first national record. Different thermal preferences of early invaders (mostly coldwater species) and new invaders (typically warmwater adapted) may benefit the latter in the face of climate change. It is concluded that new challenges for alien fish management arise and that ecosystem‐based approaches as endorsed by the E.U. Water Framework Directive (maintaining or restoring good ecological status of rivers and streams) should become the centrepiece of river management in Europe.